The Influence of the Work Environment and Organizational Culture on Teacher Performance at SD Negeri 4 Angsau - Hastuti, Hj. Puji; Uhara S.Ag, Hj. Dina (Cattleya Darmaya Fortuna, 2023)
Improving performance can be supported, among other things, by a good work environment and organizational culture. The work environment and organizational culture can influence the performance of its resources. The purpose of this research is to determine the work environment of teachers and organizational culture at SD Negeri 4 Angsau, as well as whether the work environment and organizational culture have partial or simultaneous effects on the performance of teachers at SD Negeri 4 Angsau. The method used in this research is descriptive quantitative. Data collection techniques used in this study involve secondary data and primary data. The sampling method used is non-probability sampling with a sample size of 34 individuals. This research aims to: 1) determine whether there is an influence of the work environment on teacher performance; 2) determine whether there is an influence of organizational culture on teacher performance; 3) determine whether there is an influence of the work environment and organizational culture on teacher performance. The results of this study indicate that: 1) there is a significant positive influence between the work environment and teacher performance; 2) there is a significant positive influence between organizational culture and teacher performance; 3) there is a positive influence between the work environment and organizational culture together on teacher performance.